The Influence Of Body Weight On Heavy Stud Cows Born In Bali That Maintained By Semi Intensive - gaudensius fahik (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2015)
ABSTRACT The experiment was conducted in Belu District Veterinary Office. The purpose of this study was to determine the effect of body weight on the weight of males born in Bali cattle are reared in semi-intensive. The material used in this study is the fourth head of Bali cattle stud at the age of 2-3 years and 20 with the Bali cattle breeding cycle of marriage in the first period of 2011-2013 while mating cycles in the period from 2014 to the second method used in this study is a qualitative method of data analysis is descriptive, with four treatments, ie P1 body weight of 200 Kg, 220 Kg of body weight P2, P3 body weight of 240 kg and 260 kg body weight P4 with the same repetition. The measured variable is the birth weight of Bali cattle. Data were analyzed variance based on completely randomized design (CRD). If treatment significantly then tested further by using LSD (Least Significant Difference) to distinguish the effect of the treatment. Results from this study showed that male body weight gives a significant influence (P < 0.01) on birth weight of cattle that are semi-intensive. Birth weight cattle were highest in males body weight of 260 kg with an average birth weight of 20.72 kg. Then the male body weight of 200 kg with an average birth weight of 18.41 kg, 220 kg body weight males with an average birth weight of 19.03 Kg and 240 Kg of body weight males with an average birth weight of 20.03 kg. Based on the results of this study concluded that the male body weight of 260 kg give the best contribution to the birth weight of Bali cattle are reared as semi-intensive. Suggestions from this study that the stud is one of the supporting factors to obtain the maximum birth-weight cattle stud so the selection should be done properly. Keywords: Bali cattle, stud, weight and birth weight.